FRACTIONATION OF CARBON AND OXYGEN ISOTOPES IN 13C-RICH PALAEOPROTEROZOIC DOLOSTONES IN THE TRANSITION FROM MEDIUM-GRADE TO HIGH-GRADE GREENSCHIST FACIES: A CASE STUDY FROM THE KOLA SUPERDEEP DRILLHOLE - Melezhik V.A.; Fallick A.E.; Smirnov Yu.P.; Yakovlev Yu.N. (My University, 2003)
Samples from the Kola Superdeep Drillhole (12 262 m), a deep drillhole (1060 m), and from the surface, seaprated by only around 10 km, provided a unique opportunity for direct tracing of delta13C and delta18O changes through a low- to high-grade greenschist-facies transition within impure, 13C-rich Palaeoproterozoic dolostones. The least-altered dolostones have delta13C of +9‰ and delta18O of 22‰ . The metamorphic transition is expressed by dolomite + calcite1 + quartz ± K-feldspar to tremolite + calcite2 ± dolomite ± calcite1 and defined by 13C depletion of calcite2 (c. 3.0‰ ), calcite1 (1.0-2.0‰ ) and dolomite (<1‰ ) which is associated with a Rayleigh distillation process. delta18O shows a considerable resetting in all carbonate components by around 6‰ caused by a Rayleigh distillation process coupled with isotopic exchange between the carbonates and fluids with an external source of oxygen. The retrograde alteration is expressed by the formation of quartz-chlorite veinlets within tectonically bound zones of brecciated and sheared dolostones. The maximum 18O depletion in dolomite (9‰ ) and calcite1 (c. 4‰ ) were probably controlled by infiltration into permeable zones of external fluids associated with retrograde alteration; delta13C remains largely unaffected.
Keywords: Kola Superdeep Drillhole; Palaeoproterozoic; dolomite; calcite; stable isotopes; Proterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская